Relationship Between Serum Magnesium and Parathyroid Hormone Levels in Hemodialysis Patients - رضوان فيصل (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The aim of this study is to investigate the relationship between serum magnesium and parathyroid hormone levels in hemodialysis patients . Methods: it is (Cross-Sectional) Study conducted for the period of one year(May 2019 –May 2020) at Tishreen University Hospital in Lattakia-Syria. The study included 82 patients with chronic kidney disease (CKD) undergoing hemodialysis, Laboratory analysis of magnesium and parathyroid hormone were conducted for all patients before starting the dialysis session. Results: We found in all patients normal or high serum magnesium,( 36.58 % normal , 63,42 % high), the mean of magnesium (2.78 mg/dl ) , and the mean of PTH (295 Pg/ml), we found statistically significant differences in PTH ​​between the group of patients with normal magnesium and the group with hyper magnesium (Mg>2.5 mg/dl), where the mean PTH values ​​were (339.4 ± 68 pg/ml) in the normal magnesium group, and the mean PTH was (272.3 ± 43 pg/ml) in the hypermagnesium group (P.value=0.01).We found a negative linear correlation between magnesium and PTH( r=-0.311 , p=0.03 ) . Conclusions: There is a statistically significant inverse relationship between serum magnesium and PTH